Implementasi Prinsip-Prinsip Akuntansi Syariah dalam Pengelolaan Keuangan Perusahaan - Juvent Ade Pratama; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Implementation of sharia accounting principles in company financial management is important in the current context of economic globalization. Literature studies show that these principles not only cover aspects of compliance with sharia law, but also emphasize transparency, fairness and sustainability in business practices. The application of sharia accounting principles aims to ensure that all company financial activities are in accordance with Islamic ethical values, such as the prohibition of usury, speculation and other unethical practices. This not only increases company compliance with religious laws, but can also increase trust from investors and the general public. Some of the main principles applied in sharia accounting include transparency in financial reporting, avoidance of usury, fairness in the distribution of profits and losses, as well as consideration of social and environmental aspects. By applying these principles, companies can create a business environment that is more sustainable and oriented towards the values ​​of justice. Literature studies also show that challenges in implementing sharia accounting include the lack of clear international standards, as well as complexity in the interpretation of principles that vary between countries. However, the long-term benefits of implementing these principles are expected to provide significant added value both in terms of finances and company reputation.